Non-rigid 3D Shape Classification based on Convolutional Neural Networks - Quenaya, JFL (2017)
We thank CIENCIACTIVA and their Undergraduate Thesis Program since this research has been funded by them. They have encouraged us to continue this journey and provided us with the required material to pursue our goal.